Mothers and their offspring perceive the tritone paradox in closely similar ways - DEUTSCH, Diana (Archives of Acoustics, 2007)
The tritone paradox is produced when two tones that are related by a half-octave (or tritone) are presented in succession, and the tones are so constructed that their pitch classes (C, C#, D; and so on) are clearly defined but their pitch heights are ambiguous. When listeners judge whether such tone pairs form ascending or descending patterns, their judgments show orderly relationships to the positions of the tones along the pitch-class circle: Tones in one region of the circle are heard as higher and those in the opposite region as lower. However, listeners disagree substantially as to which tones are heard as higher and which as lower, and these perceptual differences correlate with the language or dialect to which the listener has been exposed. In the present study, perceptions of mothers and their offspring were found to be strikingly similar, indicating that the mental representation influencing perception of the tritone paradox is formed early in life and survives into adulthood. It is conjectured that this mental representation is formed during the critical period in which infants acquire the features of their native language.